(untitled) (Elmergib Journal of Human Sciences, 2025)
During the Roman era, the Leptis Magna witnessed remarkable religious diversity, manifested in the spread of Roman, Greek, and Eastern symbols and worship, such as ancient Egyptian. This diversity left a clear impact on the city’s religious life, a resonance reflected in the various inscriptions and archaeological remains. Therefore, the importance of this study lies in its reliance on primary sources, such as inscriptions and archaeological evidence. This further enhances its credibility and contributes to painting an accurate picture of the nature of worship in Leptis Magna during the Roman era, especially given the scarcity of other sources. The objectives of the study are: to analyze the religious inscriptions and archaeological remains discovered in Leptis Magna, to identify the symbols worshiped in the city, and to monitor manifestations of reconciliation between ancient and Roman religions. The problem of the study: Despite the abundance of archaeological evidence and inscriptions in Leptis Magna, there is a lack of studies that address this subject from a religious perspective. Therefore, the problem of the study is represented by the following question: What Roman religious symbols enjoyed a prominent and visible presence in Leptis Magna during the Roman era, as revealed by inscriptions and archaeological data? In terms of methodology, the study will adopt the historical-analytical approach based on the analysis of various inscriptions, in addition to the descriptive approach to addressing the archaeological remains of temples and various sculptural works. The study concluded that Leptis Magna was a model for studying the interaction between different cultures during the Roman era, especially on the religious level. It revealed the extent of the diversity of deities that was a noticeable presence, and evidence also shows that some of the city’s local elements adopted Roman deities. It also indicates that the temples and all other works of art were not merely works of art, but rather a profound reflection of the extent of religiosity prevalent in the city.